Kinetics Study of the Hydrogen Reduction of Limonite Ore Using an Unreacted Core Model for Flat-Plate Particles - Jindi Huang; Tao Yi; Jing Li; Mingzhou Li; Fupeng Liu; Jinliang Wang (Metals, 2025)
The iron and steel industry is a major emitter of carbon. In the context of China’s dual-carbon goals, hydrogen-based reduction ironmaking technology has garnered unprecedented attention. It is considered a crucial approach to reducing carbon dioxide emissions in the steel sector and facilitating the realization of carbon neutrality. This work conducted isothermal thermogravimetric analysis on limonite ore in a N2/H2 atmosphere. The influences of reduction temperature, particle size, and hydrogen partial pressure on the hydrogen reduction reaction process of limonite were investigated. Based on the principles of isothermal thermal analysis kinetics and the unreacted core model for flat-plate particles, the mechanism function and kinetic parameters for the reduction of limonite particles were determined. The research results show that the hydrogen reduction process of limonite ore is influenced by multiple factors, including temperature, hydrogen partial pressure, and particle size. Increasing the reduction temperature and hydrogen partial pressure can significantly speed up the reduction reaction rate and enhance the degree of reduction. The kinetic parameters for the hydrogen reduction of limonite particles were obtained as follows: the reaction activation energy was 44.738 kJ·mol−1, the pre-exponential factor was 31.438 m·s−1, and the rate constant for the hydrogen reduction of limonite was <semantics>k=31.438×e−<mstyle scriptlevel="0" displaystyle="true">44.738×1000RT</mstyle>m⋅s−1</semantics>. In addition, contour maps were plotted to predict the reaction time and reaction temperature required for a complete reduction of limonite particles of different sizes to iron (Fe) particles under varying hydrogen partial pressures. The research findings can serve as a scientific basis for optimizing hydrogen-based reduction ironmaking technology in the iron and steel industry and achieving carbon neutrality goals.